Content-based FGS coding mode determination for video streaming over wireless networks - Hung, Bin-Feng; Huang, Chung-Lin (IEEE journal on selected areas in communications, 2003)
Video streaming is the major subject of Amendment for MPEG-4 and it is developed in response to the growing needs on a video-coding standard for the video communication. The fine-granular scalability (FGS) combined with the temporal scalability addresses a variety of challenging problems in delivering video. The FGS video encoder makes the coding mode decision based on the video content and the current available bandwidth in order to achieve higher perceptual video quality. In this paper, we develop a mode selection method to find the most suitable scalable coding mode from six coding schemes: FGS, FGST, FGS-SE, and FGST with background composition based on the contents of the video sequences.